2004
DOI: 10.1002/pmic.200400939
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis of cellular proteins extracted from highly virulent Francisella tularensis ssp. tularensis and less virulent F. tularensis ssp. holarctica and F. tularensis ssp. mediaasiatica

Abstract: Francisella tularensis is the causative agent of the zoonotic disease tularemia. Four subspecies of this pathogen, namely ssp. tularensis, mediaasiatica, holarctica, and novicida are spread throughout the northern hemisphere. Although there are marked variations in their virulence to mammals, the subspecies are difficult to identify as they are closely genetically related. We carried out the comparative proteome analysis of cellular extracts from isolates representing the highly virulent subspecies tularensis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 34 publications
5
46
1
Order By: Relevance
“…A nonsynonymous variant can alter protein structure or function, however these changes can be profitable or even neutral if the changes do not affect the protein folding or the active site. Previous works associating this different electrophoretic mobility with the pathogenic potential, demonstrated that the proteins showing shifts from more acidic position are in less virulent strains [32,33]. In the present study, the electrophoretic changes did not follow a fixed pattern; the enzymes related to the virulent strain sometimes were more basic and other times more acidic.…”
Section: Discussionsupporting
confidence: 45%
“…A nonsynonymous variant can alter protein structure or function, however these changes can be profitable or even neutral if the changes do not affect the protein folding or the active site. Previous works associating this different electrophoretic mobility with the pathogenic potential, demonstrated that the proteins showing shifts from more acidic position are in less virulent strains [32,33]. In the present study, the electrophoretic changes did not follow a fixed pattern; the enzymes related to the virulent strain sometimes were more basic and other times more acidic.…”
Section: Discussionsupporting
confidence: 45%
“…Previous Francisella proteomics studies have catalogued LVS protein profiles [29,30], immune reactive proteins [31], or stress response proteins [32]. A proteomic comparison of three Francisella strains has been performed, identifying many protein differences [33]. However, most of these were mass and charge variants of proteins present in all three strains [33].…”
Section: Discussionmentioning
confidence: 99%
“…The protein can then be identified by means of mass spectrometry. Such an approach was used for comparison between the three subspecies of F. tularensis and there were several protein spots characteristic of each subspecies (Hubalek et al, 2004). In combination with statistical methods such as principal component analysis, this method can be used for the identification of subspecies.…”
Section: Proteomicsmentioning
confidence: 99%
“…The advantage of well-characterized protein spots on the gel led to the investigation of immunogenicity of Francisella proteins in the host (Hubalek et al 2004). The resulting list of proteins points out to potential targets of immunoassays or subunit vaccines.…”
Section: Proteomicsmentioning
confidence: 99%